Field Analysis of Noise Pollution Levels in Al-Bayda City (Derna Academy Journal for Applied Sciences, 2025)
This study aims to conduct a field analysis of noise pollution levels in Al-Bayda city by measuring noise intensity at key locations including industrial workshops, event halls, schools, and residential, commercial, and industrial areas. The recorded levels were compared with the World Health Organization (WHO) standards. A Sound Level Meter was used to capture decibel levels at various distances from noise sources, and classroom experiments were conducted to evaluate the effectiveness of noise-reduction teaching strategies. The findings showed that noise levels exceeded WHO limits in most areas, particularly in industrial zones, educational facilities, and hospitals, ranging from 103 to 130 dB. A strong correlation was observed between increased reliance on generators during electricity outages and rising rates of ear-related illnesses. The study recommends enforcing global noise standards, promoting the use of silencers, applying urban planning principles, improving classroom environments, launching public awareness campaigns, and establishing a national system to monitor noise pollution regularly.